2020
DOI: 10.1038/s41598-020-59143-8
|View full text |Cite
|
Sign up to set email alerts
|

Denosumab for dialysis patients with osteoporosis: A cohort study

Abstract: Evidence for the efficacy of denosumab in HD patients is limited. Accordingly, here we report a study on the safety and efficacy of denosumab in these patients. We prospectively followed 324 patients (121 HD and 203 non-HD patients) receiving denosumab between June 2013 and May 2018, assessing changes in bone mineral density (BMD) and bone metabolic markers, and noting side-effects. Annual changes in BMD at the lumbar spine in HD and non-HD patients from baseline were, respectively, 6.7 ± 11.1% and 7.5 ± 10.2%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 20 publications
5
31
0
1
Order By: Relevance
“…We showed that TRACP-5b, BAP and ALP were associated with a large decline in serum Adj Ca levels. The results were consistent with recent cohort studies of HD patients with osteoporosis treated with denosumab 13 , 14 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We showed that TRACP-5b, BAP and ALP were associated with a large decline in serum Adj Ca levels. The results were consistent with recent cohort studies of HD patients with osteoporosis treated with denosumab 13 , 14 .…”
Section: Discussionsupporting
confidence: 92%
“…Recent studies have shown that a higher tartrate-resistant acid phosphatase-5b (TRACP-5b) level, which reflects high bone turnover, is a predictor of hypocalcaemic events 13 , 14 . However, little is known about markers for predicting the effect of denosumab.…”
Section: Introductionmentioning
confidence: 99%
“…The validity of studies investigating the efficacy of denosumab 79,[118][119][120][121][122][123][124][125][126] and bisphosphonates 79,106,[127][128][129][130] in patients with advanced CKD, including those on dialysis, or in patients with earlier CKD stages presenting with biochemical disturbances of mineral metabolism is limited by small sample sizes.…”
Section: Low Bone Turnover and Efficacy Of Antiosteoporosis Treatmentmentioning
confidence: 99%
“…Another important factor to consider is that Dmab is not contraindicated in patients with OP associated with chronic kidney damage (CKD). Dmab, unlike BPs, can be employed also in patients on hemodialysis (17). It is worth mentioning that renal impairment and haemodialysis are associated with an increased risk of hypocalcaemia, especially if proper calcium and vitamin D supplementation is not prescribed, and patients should be monitored closely for the aforementioned side effect.…”
Section: Case Reportmentioning
confidence: 99%